Change management in quality and production spheres of manufacturing companies (Journal of Economic Research & Business Administration, 2015)
The authors consider different aspects of new technology application, international standards of quality and quality management systems’ usage during implementation of changes in organizations. Various ways and approaches in order to improve production processes and quality in manufacturing companies have been described and offered. The authors of the article state that measures to improve production and quality during management of change improve the competitive advantage of production companies on the market.
Keywords: organizational changes; organizational change management; production improvement; quality improvement; “good manufacturing and hygienic practice”